Poly Royal One Last View: Archies' work to be permanent (1973)
Mustang Daily newspaper clippings accompanied by images of Cal Poly Architecture students' structures in Poly Canyon. Another clipping has a headline that reads, 'Student's air structure is first of its kind in U.S.' accompanied by a photo of the Shell House.